TRADISI NIKAH SIRI SETELAH KHITBAH DI DESA PAKALONGAN SAMPANG MADURA PERSPEKTIF MAQASHID SYARIAH - Abdul Bari Muhammad Amir, Ahmad; Sukardi, Imam (USRATUNA: Jurnal Hukum Keluarga Islam, 2022)
Islam recommends that every marriage be preceded by a proposal before a husband and wife bond occurs. This is intended so that when the marriage is carried out on the awareness and knowledge of both parties. In Madura, to be precise in Pakalongan Sampang Village, Sampang District, Sampang Madura Regency, there are many practices of sermons and unregistered marriages which have become a hereditary tradition. Proposals and marriage contracts are common there. This research is a qualitative research, data taken systematically from the field. The data will then be analyzed using maqashid sharia principles in Islam. The results of the study revealed that most of the people of Pekalongan Village, Sampang Subdistrict, already knew the post-khitbah siri marriage tradition and understood that there were lessons to be learned from the post-khitbah siri marriage tradition. Siri marriage after the khitbah in Pakalongan village is legally permissible, it can even become mandatory if there is a potential for adultery after the khitbah. And in maqashid syari'ah terms, unregistered marriage after khitbah is in accordance with five basic principles, namely protecting religion (hifdzu al-din), protecting life (hifdzu al-nafs), protecting offspring (hifdzu al-nasl), protecting property (hifdzu al-nafs), guarding wealth (hifdzu al-mal), and guarding the mind (hifdzu al-'aql).